Improving the stability of tonal track circuits under fluctuations of ballast resistance - Honcharov, K. V. (Science and Transport Progress, 2013)
Purpose.The purpose of investigation is the development of method for improving the stability of tonal track circuits that takes into account the actual insulation resistance (ballast resistance) of rail line.Methodology. To achieve the research purpose it was proposed to automatically determine the insulation resistance of rail line, and depending on this value to adjust the output voltage of track generator. Ballast resistance is determined by the value of input resistance the rail line, which at high frequencies practically is equal to the wave impedance. To implement the proposed method it is necessary to connect to the track circuit additional high-frequency generators, high-frequency filters, unit for finding the ballast resistance and adjusting the output voltage of track generator. Findings. As a result of research it was found that at low values (less than 2 Ohms*km) the change of ballast resistance causes significant change of voltage at the track receiver input, which may cause malfunction of the track circuit. Increasing the length of rail line leads to the reducing of its input resistance, raising the measuring frequency causes increasing the input resistance. In both cases, the input resistance tends to the value of the wave impedance. The measuring frequency should be chosen taking into account the length of rail line and the upper limit of ballast resistance, the value 5 Ohms*km can be taken as that limit. At higher values of ballast resistance its changes insignificantly influence the input voltage of track receiver. In this case, the adaptive adjustment of voltage at the track generator output is not performed. Originality. The method for measuring the insulation resistance of rail line has been improved that allows one to determine the ballast resistance automatically. The dependence between measuring frequency, length of rail line and ballast resistance have been determined. Practical value. The proposed method allows one to improve the reliability of tonal track circuits, to provide their stable operation under fluctuations of ballast resistance due to determination of the actual insulation resistance of rail line and the adaptation of track circuits to the actual conditions of their operation.